Strategi dalam Menajaga Ketahanan Keluarga Bagi Penyandang Disabilitas (Studi Kasus di Kecamatan Candung, Kabupaten Agam Propinsi Sumatera Barat) - Dahyul Daipon; Abul Khair (USRATY : Journal of Islamic Family Law, 2023)
The title of this research is "The Efforts of a Husband and Wife with Disabilities in Forming a Sakinah Family (Case Study in Cdung District, Agam Regency)." The author, Abul Khair, discusses the sakinah family, which includes understanding each other, exercising rights and obligations, providing peace, love and happiness among family members. This study aims to determine the efforts of married couples with disabilities in creating a sakinah family. The research method used was field research in Cdung District, Agam Regency, with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that five couples with disabilities succeeded in creating a sakinah family. In forming a sakinah family, several important factors were found, including compatibility between husband and wife, partnership, complementing each other's weaknesses, accepting each other's strengths and weaknesses, supporting each other, and carrying out God's commands. Even though they have physical limitations, marriages between people with disabilities bring the same spirit of struggle in building a family life. This encourages married couples with disabilities to create a sakinah family, because they feel that they have physical equality and equality in deficiencies, thus proving that harmony in a marriage does not depend on physical conditions, can be one word or compound words.